2017
DOI: 10.1002/iub.1614
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting copper homeostasis in diabetes mellitus

Abstract: Diabetes Mellitus (DM) is characterized by elevated blood glucose levels (hyperglycemia). It can occur due to impaired secretion or action of the hormone insulin, which is produced by pancreatic beta-cells to promote the entry of glucose into the cells. It is known that hyperglycemia has an important role in the production of reactive oxygen species in all types of DM and that an imbalance of transition metal as Cu and Fe plays a pivotal role in stimulating the oxidative stress. Different levels of some transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 66 publications
(83 reference statements)
1
49
0
1
Order By: Relevance
“…Transition between Cu(I) and Cu(II) leads to the production of reactive oxygen species (ROS) and to consequent peroxidation of lipids, DNA damage leading to cell death. Therefore, copper homeostasis maintenance using copper chelators may represent a strategy for diabetes treatment [16]. A series of pre-clinical and clinical studies demonstrated the potential of trientine in reducing some of the clinical and pathological consequences of diabetes, such as heart failure [88].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Transition between Cu(I) and Cu(II) leads to the production of reactive oxygen species (ROS) and to consequent peroxidation of lipids, DNA damage leading to cell death. Therefore, copper homeostasis maintenance using copper chelators may represent a strategy for diabetes treatment [16]. A series of pre-clinical and clinical studies demonstrated the potential of trientine in reducing some of the clinical and pathological consequences of diabetes, such as heart failure [88].…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…ATPase copper-transporting alpha (ATP7A) and ATPase copper-transporting beta (ATP7B) are key players in copper homeostasis being required for copper delivery to the secretory pathway and for efflux of excess copper from the cell. Deregulation of this delicate balance that maintains copper homeostasis has been associated with The aim of the present review is to provide a global overview on the main different chelation therapy approaches which have been evaluated for the treatment of the diseases in which copper imbalance has a key role in the onset of the pathology, including genetic diseases of copper metabolism such as Wilson's diseases [8], neurodegenerative diseases such as Alzheimer's and Parkinson's diseases [14], idiopathic pulmonary fibrosis [15], diabetes [16], and different forms of cancer [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent results indicate that altered serum Cu homeostasis has an important role in diabetes, obesity, metabolic syndrome and non-alcoholic fatty-liver disease (NAFLD). 25,26 In fact, diabetes mellitus and obesity are known to correlate with an imbalance of transition metals, including Cu. 27 Oxidative stress, insulin resistance, end-product molecules, adipokines, pro-inflammatory cytokines and mitochondrial dysfunction are all related to higher Cu serum levels and are implicated in the development and progression of several chronic inflammatory diseases.…”
Section: Cu and Metabolic Diseasesmentioning
confidence: 99%
“…•− , whereas interaction with H 2 O 2 may generate OH˙in the Fenton and Haber-Weiss reactions [11]. The transition of Cu(I) and Cu(II) may result in the generation of ROS and it may further lead to the oxidation of protein and other molecules [12,13].…”
Section: Introductionmentioning
confidence: 99%